Cholera toxin B subunit: an efficient transmucosal carrier-delivery system for induction of peripheral immunological tolerance. - Sun, J B (1994)
Oral administration of antigens, including allergens and autoantigens, may be an efficient way to prevent diseases associated with untoward immune responses to self- and non-self-antigens. However, this approach has met with limitations because it usually requires repeated administrations of large doses of antigen and is less efficient in an already immune host, and the effect is of short duration. We report that a single oral administration of minute amounts of particulate or soluble antigen coupled to the B subunit of cholera toxin (CTB) can markedly suppress systemic immune responses in naive and in systemically immune animals. Both early (2-4 hr) and late (24-48 hr) delayed type-hypersensitivity reactivities were strongly suppressed after feeding a single dose of CTB-conjugated antigen. Serum antibody responses were also decreased, although moderately, after oral administration of CTB-conjugated antigen. This strategy of tolerance induction, based on oral administration of small amounts of antigens conjugated to a mucosa-binding molecule, may find broad applications for preventing or abrogating untoward immune responses.